2020
DOI: 10.1002/ajhb.23457
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to studying plasticity in growth disruption and outcomes: A bioarchaeological case study of Napoleonic soldiers

Abstract: Objectives The aim of this study was to investigate how much variation in adult stature and body mass can be explained by growth disruption among soldiers who served in Napoleon's Grand Army during the Russian Campaign of 1812. Methods Linear enamel hypoplasia (LEH) were recorded as representations of early life growth disruption, while the impact on future growth was assessed using maximum femur length (n = 73) as a proxy for stature and maximum femoral head diameter (n = 25) as a proxy for body mass. LEH fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…For example, porotic hyperostosis (porous lesions on the cranial vault) and cribra orbitalia (porosity on the orbital roof) reflect a history of bone marrow hypertrophy or hyperplasia resulting from one or more periods of infection, metabolic deficiencies, malnutrition, and/or chronic disease ( 21 26 ). Meanwhile, linear enamel hypoplasia (transverse areas of reduced enamel thickness on teeth) occurs in response to similar childhood physiological stressors (e.g., disease, metabolic deficiencies, malnutrition, weaning) that disrupt enamel formation in the developing permanent dentition ( 27 30 ). Broadly, these paleopathological indicators of childhood stress tend to be observed at higher rates among individuals from initial farming communities relative to earlier periods, potentially reflecting their overall “poorer” health ( 14 , 31 36 ).…”
mentioning
confidence: 99%
“…For example, porotic hyperostosis (porous lesions on the cranial vault) and cribra orbitalia (porosity on the orbital roof) reflect a history of bone marrow hypertrophy or hyperplasia resulting from one or more periods of infection, metabolic deficiencies, malnutrition, and/or chronic disease ( 21 26 ). Meanwhile, linear enamel hypoplasia (transverse areas of reduced enamel thickness on teeth) occurs in response to similar childhood physiological stressors (e.g., disease, metabolic deficiencies, malnutrition, weaning) that disrupt enamel formation in the developing permanent dentition ( 27 30 ). Broadly, these paleopathological indicators of childhood stress tend to be observed at higher rates among individuals from initial farming communities relative to earlier periods, potentially reflecting their overall “poorer” health ( 14 , 31 36 ).…”
mentioning
confidence: 99%
“…Therefore, another factor to consider is the timing of defect formation and its association with mortality risks. Recent research demonstrated how variation in adult stature and body mass relates to the timing and severity of early growth disruptions (LEH) as well biocultural factors, such as height requirements (Holder et al, 2020). Additionally, the microscopic analysis of the LEH has shown that earlier ages‐at‐first‐defect formation are associated with increased risks of mortality as well as an increased likelihood of future defects (Temple, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot directly address the role that culture and society played in each person's health outcomes. Nevertheless, we must highlight that the skeleton and, to some extent, the dentition are plastic in their responses to cultural and biological inputs (e.g., Berger et al, 2020; Holder et al, 2020; Kuzawa, 2007).…”
Section: Discussionmentioning
confidence: 99%